Improving Student Learning Outcomes in Islamic Education and Character Education Learning through Wordwall Applications at SMP Negeri 1 Sosa Timur - Wulandari, Nanda Ugig; Mustofa, Asyik; Priyatni, Ida; Azizah, Zuhrotul; Nengsih, Wahyu (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning outcomes of class VII-1 students in the Islamic Religious Education and Character Education Subject, especially the Asmaul Husna material, through the use of the Wordwall application at SMP Negeri 1 Sosa Timur, Padang Lawas Regency. The Wordwall application was chosen because it can present interactive and interesting learning, so it is expected to increase student motivation and understanding. This study uses a classroom action research (CAR) method with two cycles including planning, implementation, observation, and reflection. Data were obtained through student learning outcome tests, observations, and interviews. The results of the study showed a significant increase in student learning outcomes after using the Wordwall application. This is reflected in the increase in the average score of student learning outcome tests and the increase in active student participation in the learning process. In addition, students gave a positive response to the use of this application, which was considered fun and made it easier for them to understand the material. Thus, it can be concluded that the Wordwall application is effective in improving student learning outcomes in the Asmaul Husna material at SMP Negeri 1 Sosa Timur, Padang Lawas Regency, and can be an alternative interesting and innovative learning method.